Sleep-wake, cognitive and clinical correlates of treatment outcome with repetitive transcranial magnetic stimulation for young adults with depression. (January 2019) - Kaur, Manreena; Naismith, Sharon L; Lagopoulos, Jim; Hermens, Daniel F; Lee, Rico S C; Carpenter, Joanne S; Fitzgerald, Paul B; Hoy, Kate E; Scott, Elizabeth M; Hickie, Ian B
Highlights: Depressive and anxiety symptoms were reduced with rTMS treatment for young adults with current depression. Better cognitive flexibility and verbal learning were associated with greater improvements in depressive symptoms with rTMS treatment. A later age of onset and greater number of depressive episodes were associated with greater improvements in depressive symptoms with rTMS. This research provides some support for the use of cognition in predicting rTMS response and for further evaluation of rTMS as an early intervention for depression. Abstract: The utility of key phenotypes of depression in predicting response to repetitive transcranial magnetic stimulation (rTMS), namely sleep-wake behaviour, cognition and illness chronicity, has been understudied and not been extended to young samples. This study aimed to determine whether sleep-wake disturbance, cognition or depression chronicity are associated with rTMS outcome in young depressed adults. Sixteen depressed young adults diagnosed with mood disorders (aged 18–29 years) completed this open-label study. Neuronavigationally targeted high-frequency rTMS was administered at 110% of motor threshold on the left dorsolateral prefrontal cortex for 20 sessions over 4 weeks. Clinical, sleep-wake and cognitive assessments were undertaken pre- and post-treatment. Repeated-measures and correlational analyses determined pre- and post-treatment changes and predictors of treatment outcome. rTMS significantly reduced depression and anxiety. Better cognitive flexibility, verbal learning, later age of onset and greater number of depressive episodes were associated with better treatment outcome. There were no other significant/trend-level associations. rTMS had no effect on sleep-wake or cognitive measures. We provide the first evidence for the utility of cognitive flexibility and verbal learning in predicting rTMS outcome in depressed young adults. This research provides preliminary support for rTMS as an early intervention for depression and supports the need for sham-controlled trials.